Efeito do pastoreio rotativo sobre a composição florística e estrutural de uma pastagem natural do bioma Pampa, Santa Maria, RS - Seibert, Liane (2015)
The objective of this study was to evaluate the effect of rotational grazing on the floristic composition and structure of a natural grassland of Pampa biome. The study comprises the periods of spring / summer of three years (2011, 2012 and 2013) in an experimental site at Depressão Central of Rio Grande do Sul state. Treatments were two rest intervals under rotational grazing, 375 degree days (DD) and 750 degree-days (DD), the experimental design was randomized blocks with three replications, with repeated measures over time. The blocking factor was the proportion of the top, slope and lowland relief at each repetition. Records were analyzed as a three-year data base and subjected to ordination analysis and randomization testing using MULTIV software. There was no significant difference for the variables assessed over the three assessment periods. The evaluated rest intervals on rotational grazing didn t affect structure and floristic composition of a natural grassland during the spring / summer over the three years of evaluation.